Analisis Proyek Poster pada Indikator Novelty dalam Model PjBL Mata Pelajaran PAI-BP di Kelas XI SMAN 2 Lubuk Sikaping - Putri, Viona Yolanda; Muliati, Indah (Lembaga Yasin AlSys, 2025)
This study is motivated by the low creative capacity of students in delivering religious messages in an engaging and original manner, thus necessitating an analysis of their work, particularly poster projects developed through the Project Based Learning (PjBL) model. The study aims to analyze the novelty aspects of five educational posters created by eleventh-grade students at SMAN 2 Lubuk Sikaping during Islamic Religious Education learning. Using a qualitative approach and content analysis method, five posters themed “Avoiding Student Fights, Alcohol, and Drugs” were examined based on new ideas, visual symbols, and message approaches that are both informative and creative. The results indicate that although the selected themes are relatively common, students were able to present new perspectives through metaphorical visualizations, religious approaches, and meaningful contextual slogans. Novelty is evident in the students' ability to connect Islamic values with the realities of youth life, such as symbolizing impaired reasoning with an image of a grenade or highlighting the prohibition of praying while intoxicated based on Qur’anic verses. The emphasis on novelty in these works reflects students’ critical and creative thinking skills in conveying religious messages through visual media and indicates the potential of the PjBL model in fostering religious expression that is both relevant and appealing to young audiences.